UVA irradiation of riboflavin generates oxygen-dependent hydroxyl radicals - Sel, Saadettin; Naß, Norbert; Pötzsch, Sandy; Trau, Stefanie; Simm, Andreas; Kalinski, Thomas; Duncker, Gernot; Kruse, Friedrich E.; Auffarth, Gerd U.; Brömme, Hans-Jürgen (Redox report, 2014)
UVA, Riboflavin, Electron spin resonance, 5, 5-Dimethyl-1-pyrroline N-oxide, Spin trapping, Hydroxyl radical, Hydrogen peroxide, Catalase, UV-VIS spectroscopy, High-performance liquid chromatography